Global Sex Trade and Women Trafficking in Nigeria (2011)
Academic discourses and policy debates on the phenomenon of women trafficking have focused on the threat of illegal migration, migration management, and the stereotypical linkages between criminality and migration. Such themes neglected the perspectives of trafficking victims and the social context, most especially closed borders and poverty. Obviously, women trafficking constitute one of the anxieties and disruptive effects of globalization. For many women, migration across the polarized economy under the regime of globalization is associated with exploitation, criminalization, and insecurity. This paper argues that trafficking in women reflects inequality on a global scale: transfer of resources from depressed economy to prosperous economy, from the periphery to the core, and from rural to urban areas. There is a thriving market for trafficking in women to Europe for sexual purposes, as economic motivations, organized global syndicates, poverty, and patriarchal pressures have ensured steady supply of women in the global sex industry. Despite the political will, the weakening influence of the Nigerian government in the global economy and international diplomacy, as well as porous borders, undermines its efforts in rolling back women trafficking.